2021
DOI: 10.1016/j.ygcen.2020.113544
|View full text |Cite
|
Sign up to set email alerts
|

Fish reproductive biology – Reflecting on five decades of fundamental and translational research

Abstract: Driven by the broad diversity of species and physiologies and by reproduction-related bottlenecks in aquaculture, the field of fish reproductive biology has rapidly grown over the last five decades. This review provides my perspective on the field during this period, integrating fundamental and applied developments and milestones. Our basic understanding of the brain-pituitary-gonadal axis led to overcoming the failure of farmed fish to ovulate and spawn in captivity, allowing us to close the fish life cycle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 195 publications
(202 reference statements)
0
25
0
1
Order By: Relevance
“…Crowding factors have been supposed to exert an inhibitory effect on growth and reproduction and to depress heart rate (Pfuderer et al., 1974 ). Sex steroids made hydrophilic through glucuronide and sulphate conjugation and excreted to the water through fish urine, free steroids released through the gills (Zohar, 2021 and references therein cited) as well as prostaglandin F2α (Mylonas et al., 2017 ) are well‐known pheromones that facilitate successful reproduction and spawning by synchronizing reproductive activity. However, to our knowledge, the identity of purported pheromones acting as reproduction inhibitors in high‐density rearing conditions have not been discovered yet.…”
Section: Factors Inducing Follicular Atresiamentioning
confidence: 99%
“…Crowding factors have been supposed to exert an inhibitory effect on growth and reproduction and to depress heart rate (Pfuderer et al., 1974 ). Sex steroids made hydrophilic through glucuronide and sulphate conjugation and excreted to the water through fish urine, free steroids released through the gills (Zohar, 2021 and references therein cited) as well as prostaglandin F2α (Mylonas et al., 2017 ) are well‐known pheromones that facilitate successful reproduction and spawning by synchronizing reproductive activity. However, to our knowledge, the identity of purported pheromones acting as reproduction inhibitors in high‐density rearing conditions have not been discovered yet.…”
Section: Factors Inducing Follicular Atresiamentioning
confidence: 99%
“…Besides, DA was found to inhibit GnRH releasing in goldfish ( Carassius auratus ) (Trudeau, 1997) and inhibit both FSH and LH secretion, but no concomitant effects on GTH synthesis in rainbow trout ( Oncorhynchus mykiss ) (Vacher et al, 2002). DA antagonists (DOM or PIM), which can competitively bind to DA receptor 2 and relieve the inhibitory effect of DA, and are widely used for artificial reproduction in fish (Roche et al., 2018; Zohar, 2021). Combined with DOM and GnRHa treatment, an increase in GtH subunit expression has been reported in zebrafish, sablefish, and catfish ( Heteropneustes fossilis ) (Acharjee et al., 2017; Fontaine et al., 2013; Guzmán et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although not experimentally demonstrated, combining the available endocrine research from other fish and greater amberjack, one can hypothesize that the reproductive dysfunction is related to an insufficient release of LH from the pituitary at the conclusion of oogenesis (Mylonas et al 1997(Mylonas et al , 1998(Mylonas et al , 2010. This in turn is caused by a dysfunctional release of GnRH from the hypothalamus (Zohar et al 2010;Zohar 2020). This hypothesis is in agreement with (i) the evidence that both liver vitellogenin gene expression and oocyte yolk accumulation are not impaired (Pousis et al 2018) and fully vitellogenic oocytes are commonly found in the ovary of captive-reared fish (Mylonas et al 2004;Fern andez-Palacios et al 2015a;Nyuji et al 2016;Zupa et al 2017b;Jerez et al 2018;Pousis et al 2018;Sarih et al 2018;Fakriadis et al 2019Fakriadis et al , 2020aFakriadis et al , 2020b, (ii) the absence of a peak in LH plasma concentration following the increase in pituitary lhb gene expression (Nyuji et al 2016) and (iii) the low capacity of females to complete oogenesis and spawn spontaneously (Jerez et al 2018;Sarih et al 2018).…”
Section: Hormonal Manipulations Of Reproductive Function and Induced Spawningmentioning
confidence: 99%